Characteristics of ash particles from the maar complex of Lamongan Volcanic Field (LVF), East Java, Indonesia: How textural features and magma composition control ash morphology - Gurusinga, Muhammad Andriansyah; Ohba, Tsukasa; Harijoko, Agung; Hoshide, Takashi (Volcanica, 2023)
The Lamongan Volcanic Field (LVF), East Java, Indonesia, has experienced numerous maar eruptions, producing varied properties and morphologies of ash particles. This study conducted textural, morphometric, and geochemical analyses of the juvenile particles to elucidate the factors governing their heterogeneous characteristics. Two distinct types of juvenile ash were identified: A (black and brown ash) and B (orange-brown ash), reflecting different fragmentation processes. The blocky to slightly elongate shapes of juvenile A across heterogenous basaltic compositions (resulting in variable textures, rheological properties, and/or cooling histories) highlight the phreatomagmatic process as the primary control of their shape. In contrast, the irregular-fluidal shapes of juvenile B particles indicate magmatic fragmentation of basaltic andesite magma. This study reveals that variable magma properties yield diverse ash components, yet fragmentation dynamics govern pyroclast shapes in the LVF maar complex. Our integrated approach emphasizes the importance of considering multiple variables when interpreting heterogeneous volcanic ash deposits.